Analysis on the errors and omissions in the Finnish balance of payments: restless capital movements, floating exchange rate and errors since 1991 - Jorma Hilpinen (Bank of Finland, 1995)
The pressures on the markka's exchange rate caused substantial swings in capital movements during 1991 and 1992.The markka was let to float in September 1992, and since then exchange rate changes have been volatile. The Bank of Finland has complete monthly information for the BoP statistics since January 1991, allowing the calculation of detailed capital movements as well as a proper monthly errors and omissions item.The information system was planned in fixed exchange rate circumstances.The last four years have challenged the system more than expected, raising the risk of major errors and omissions. The early data on current account is one item of economic information most eagerly awaited.The period of exchange rate turbulences also posed many practical problems in recording visible- and invisible current account transactions. In view of quality of the BoP-statistics measured with the errors and omissions, the last four years of exchange rate turbulence did not cause outstanding errors and thus a sudden weakening in the quality of statistics. In the circumstances of floating currencies in many European countries the need and scope for revisions of early indicators of current account and other items may increase.So far our error even in the first current account estimates has been moderate, though it has been systematic, and the estimates have given a fairly reliable picture of the developments of the foreign stability of the Finnish economy.
URN:NBN:fi:bof-20140807120
Keywords: 330